A dual-responsive luminescent metal–organic framework as a recyclable luminescent probe for the highly effective detection of pyrophosphate and nitrofurantoin12. Issue 15 (26th June 2019) - Li, Hui; Ren, Jie; Xu, Xiufang; Ning, Liangmin; Tong, Ruoyan; Song, Yao; Liao, Shengyun; Gu, Wen; Liu, Xin
Abstract : Luminescent ZTMOF-1 can discriminately detect PPi and NFT with high selectivity, sensitivity and stability. Abstract : Pyrophosphate (PPi) is a significant biological anion, and its abnormal level in the human body is regarded as a signal of some diseases. Herein, we developed a method for the detection of PPi using a luminescent ZTMOF-1 via the luminescence turn-on effect. PPi formed hydrogen bonds with the phenyl and pyridine rings in the framework, and ZTMOF-1 could discriminately detect PPi among other phosphorus oxides in both an aqueous solution and a physiological environment. In addition, to the best of our knowledge, this is the first report on the use of a regenerable MOF-based luminescent sensor for the detection of PPi. Moreover, ZTMOF-1 showed an excellent luminescence quenching response to nitrofurantoin (NFT) over other drugs with the detection limit of 0.175 μM. This study presents a dual-responsive regenerable luminescent probe for the detection of PPi and NFT.